LncIRS1 controls muscle atrophy via sponging miR‐15 family to activate IGF1‐PI3K/AKT pathway. Issue 2 (30th January 2019) - Li, Zhenhui; Cai, Bolin; Abdalla, Bahareldin Ali; Zhu, Xuenong; Zheng, Ming; Han, Peigong; Nie, Qinghua; Zhang, Xiquan
Abstract: Background: Recent studies indicate important roles for long noncoding RNAs (lncRNAs) in the regulation of gene expression by acting as competing endogenous RNAs (ceRNAs). However, the specific role of lncRNAs in skeletal muscle atrophy is still unclear. Our study aimed to identify the function of lncRNAs that control skeletal muscle myogenesis and atrophy. Methods: RNA sequencing was performed to identify the skeletal muscle transcriptome (lncRNA and messenger RNA) between hypertrophic broilers and leaner broilers. To study the 'sponge' function of lncRNA, we constructed a lncRNA‐microRNA (miRNA)‐gene interaction network by integrated our previous submitted skeletal muscle miRNA sequencing data. The primary myoblast cells and animal model were used to assess the biological function of the lncIRS1 in vitro or in vivo . Results: We constructed a myogenesis‐associated lncRNA‐miRNA‐gene network and identified a novel ceRNA lncRNA named lncIRS1 that is specifically enriched in skeletal muscle. LncIRS1 could regulate myoblast proliferation and differentiation in vitro, and muscle mass and mean muscle fibre in vivo . LncIRS1 increases gradually during myogenic differentiation. Mechanistically, lncIRS1 acts as a ceRNA for miR‐15a, miR‐15b‐5p, and miR‐15c‐5p to regulate IRS1 expression, which is the downstream of the IGF1 receptor. Overexpression of lncIRS1 not only increased the protein abundance of IRS1 but also promoted phosphorylation level of AKT (p‐AKT) a central component of insulin‐like growth factor‐1 pathway. Furthermore, lncIRS1 regulates the expression of atrophy‐related genes and can rescue muscle atrophy. Conclusions: The newly identified lncIRS1 acts as a sponge for miR‐15 family to regulate IRS1 expression, resulting in promoting skeletal muscle myogenesis and controlling atrophy.